Urbanisation process and the prevalence of tuberculosis in Malaysia - Khairiah Salwa Mokhtar; Nur Hairani Abd Rahman (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Malaysia’s rapid urbanisation process had brought about unwelcomed consequences such as environmental pollution and health issues. This study focuses on the prevalence of tuberculosis infection in Malaysia due to the urbanisation process. It utilises qualitative methods in gaining data and information needed including accessing university library databases . It was found that urbanisation had created high density housing areas like squatters and high rise flats that were susceptible to disease contagions because of their poor ventilation. Urbanisation had also brought about new places of high people concentration such as shopping complexes, public transport terminals, public buildings, educational places, and public recreational areas which all stood to increase the chances of disease infection. Finally, urbanisation had brought in foreign workers from relatively TB prone countries such as Indonesia, the Philippines, India, Bangladesh and Myanmar. The study concludes with a number of recommendations in addressing the TB prevalence issues including more rigorous monitoring of high-risk areas as well as enforcement of related rules and regulations.